Business Valuation : an The Integrated Theory. - Mercer, Z. Christopher (John Wiley & Sons, 2007)
The first book to show business appraisers why they do what they do and how everything is interrelated. Helping readers understand the why of business valuation, this book assembles the various valuation concepts into a theoretically and practical.